Energy Transitions in Nigeria: The Evolution of Energy Infrastructure Provision (1800–2015) - Norbert Edomah; Chris Foulds; Aled Jones (Energies, 2016)
The provision of energy infrastructure is essential for economic growth, social cohesion, and environmental sustainability. Understanding the multiple functions and services it provides us requires firstly a deeper understanding of the factors that influence energy infrastructure itself. This paper focusses on the factors that influence the evolution of energy infrastructure in Nigeria. By studying different eras of energy use according to the technologies that were being implemented, resources that were available, and the political practice of the time it is possible to better frame the drivers of energy infrastructure. The paper explores the transitions of how Nigerians managed to obtain the vast majority of energy from food calories and traditional biomass, to the broad portfolio of energy sources that is in use today.